Comment écrire le viol ? - Clément, Éric (La Presse+, 2018)
Le sujet est délicat. Tellement que plusieurs personnes contactées ont refusé de se prononcer sur cette nouvelle prise de conscience qui découle des mouvements #moiaussi et #agressionnondénoncée. Les romanciers doivent-ils s’autocensurer pour respecter une nou
Keywords: Bibliographie; Nettoyer

Sexual Harassment and Violence at Music Concerts and Festivals - Heen, Miliaikeala Sj.; Lieberman, Joel D. (Center for Crime and Justice Policy, 2018)
Publisher: 6876
Keywords: Bibliographie; Nettoyer

Université de Montréal: briser l'omerta - Elkouri, Rima (La Presse, 2018)
Keywords: Bibliographie; Nettoyer

Représentation du viol en littérature: pour dire quoi? - Boisclair, Isabelle (Le Devoir, 2018)
Keywords: Bibliographie; Nettoyer

Danse #WeToo - Ferron, Geneviève C. (Regroupement québécois de la danse, 2018)
// English version Depuis l’émergence du mouvement #metoo en octobre dernier, plusieurs femmes artistes du Québec ont pris la parole pour dénoncer le harcèlement, l’intimidation et les abus dont elles ont été victimes ou témoins dans le cadre de leur […]
Keywords: Bibliographie; Nettoyer

Orchestres symphoniques: une parité favorisée par un processus à l'aveugle - Larochelle, Samuel (La Presse, 2018)
Femmes et hommes côte à côte dans les orchestres symphonique d'ici. La question de parité est souvent lié au processus de sélection à l'aveugle des musiciens, une façon de faire qui permet de mettre de l'avant le talent, et ce, peu importe le sexe des artistes.
Keywords: Bibliographie; Nettoyer

900 000 $ pour contrer les agressions sexuelles et le harcèlement dans le milieu culturel québécois - Ministère de la Culture et des Communications (Gouvernement du Québec, 2018)
Keywords: Bibliographie; Nettoyer

Sexisme en danse : le mur du silence s’effrite au Québec - Carpentier, Mélanie (Jeu : revue de théâtre, 2018)
Un article de la revue Jeu, diffusée par la plateforme Érudit.
Publisher: Cahiers de théâtre Jeu inc.
Keywords: Bibliographie; Nettoyer

Une nouvelle décrivant un viol entraîne la démission de la directrice de la revue «XYZ» - Caillou, Annabelle (Le Devoir, 2018)
Vanessa Courville a claqué la porte de la revue consacrée à la nouvelle littéraire.
Keywords: Bibliographie; Nettoyer

Comment parler des violences faites aux femmes en littérature? - Caillou, Annabelle (Le Devoir, 2018)
Trois spécialistes se penchent sur le sujet. Analyse.
Keywords: Bibliographie; Nettoyer

Modèle de politique pour la création d'un milieu de travail sain, respectueux et exempt de discrimination, de harcèlement et de violence - Labine, Lise; Lorquet, Me Sébastien (L’Association des théâtres francophones du Canada, 2018)
L’Association des théâtres francophones du Canada a développé ce modèle de politique pour ses compagnies membres avec l’appui de Théâtre Action.
Keywords: Bibliographie; Nettoyer

Intégrer les personnes trans en milieu de travail - Fondation émergence; Aide aux Trans du Québec (ATQ) (2018)
Keywords: Bibliographie; Nettoyer

Code de conduite - Industries créatrices du Canada (lirelecode.ca, 2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer

Un enseignant de l'École nationale de cirque accusé de crimes sexuels - Radio-Canada (Radio-Canada, 2018)
L'entraîneur Marcelo Berti Marques fait face à quatre chefs d'accusation, entre autres pour avoir envoyé une photo de ses organes génitaux à un de ses anciens élèves de l'École nationale de cirque, à Montréal. Sa présumée victime est soulagée, mais craint qu'il ait fait d'autres victimes.
Keywords: Bibliographie; Nettoyer

The Morality of Musical Men: From Victorian Propriety to the Era of #MeToo - Shaver-Gleason, Linda (2018)
Keywords: Bibliographie; Nettoyer

Musical genius and/or nasty piece of work? Dealing with violence and sexual assault in accounts of popular music’s past - Strong, Catherine; Rush, Emma (Continuum, 2018)
For many years, the mistreatment of women in particular has essentially been normalized in many parts of the music industry. In recent years, however, there has been an increase in women coming forward and telling their stories, and asking that men be held accountable for wrongdoing. This interdisciplinary (sociology and philosophy) paper pursues two key feminist questions prompted by recent developments. Firstly: How has the construction of the history of popular music legitimated the continuation of this situation? ‘Looking back’ historically and sociologically, examples are provided of the legitimation or ignoring of violence against women (VAW) in the history of popular music to date. Secondly: How should we [archivists, historians, heritage curators and popular music educators], from now on, construct the history of popular music in a way that doesn’t legitimate VAW? Turning to ‘look forward’, applied ethics frameworks are used to explore different aspects of this second question.
Keywords: Bibliographie; Nettoyer

Encouraging Safer and More Supportive Working Practices in Theatre - Society of London Theatre; UK Theatre (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Performing Arts Training in the Age of #MeToo - Spencer, Jennifer (Voice and Speech Review, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Line Drawn Summit and Survey Report - Stone, Meg (Impact, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Facing (and Fixing) the Problem of Sexual Harassment in Theatre - Lehman, Stefanie Maiya; Morris, Celestine (Southern Theatre, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Harassment and bullying in the theatre industry: a report - The Stage (The Stage, 2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Examining the Embodied Learning Experiences about Gender in Gay and Bisexual Male Actors - McCadden, Ted; Wright, Robin Redmon (2018)
Keywords: Bibliographie; Nettoyer; Raphaël

Facing Sexual Harassment and Abuse in the Feminizing Museum - trivedi, nikhil; Wittman, Aletheia (Journal of Museum Education, 2018)
Despite the growing number of women in museums, the undervaluing of educational work traditionally associated with women, and labor largely done by women today, persists. This begs the question: in what other ways are women and femmes working in museums undermined despite their growing presence as workers and the emerging centrality of the educational role of museums? In society more broadly, we see how undervaluing women and their labor leads to a spectrum of treatment that can be considered violent. In this spectrum, we include pay and benefit disparities, disempowerment, and marginalization through sexist, homophobic, and transphobic comments and objectification, harassment, threats, verbal, physical, emotional, and financial abuse, and at the far end of the spectrum sexual assault and murder. In this article, we discuss data collected through a survey conducted about incidences of sexual abuse and harassment experienced by museum workers. We explore the results of the survey in relation to the gender-based division of labor and skills among the museum workforce. We look to the responses to this survey as a gauge of how much power women and gender non-conforming people have in their daily work lives in museums and propose actions that could increase empowerment and support.
Keywords: Bibliographie; Myriam; Nettoyer; Sexual violence; feminization; gender equity; labor; museum education; museum workers

Politique visant à prévenir et à combattre les violences à caractère sexuel - École nationale de cirque - Montréal (2018)
Keywords: Bibliographie; Coffre à outils; Dans le rapport; Nettoyer; Sophie-Anne

Post Weinstein: gendered power and harassment in the media industries - Cobb, Shelley; Horeck, Tanya (Feminist Media Studies, 2018)
Keywords: #MeToo; Bibliographie; Irina; Nettoyer

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec – Sommaire 2018-2: Données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Keywords: Bibliographie; Humour; Nettoyer; Sophie-Anne; Types de VACS